FACTORS AFFECTING THE DEVELOPMENT OF SMALL AND MEDIUM INDUSTRY BUSINESS IN MALANG CITY - Puspaningrum, Astrid (Jurnal Aplikasi Manajemen, 2019)
The purpose of this study is to explain the influence of the quality of human resources, marketing systems and partnerships on the development of SMEs. The research population is SMEs engaged in the business of processed food and beverage products in Malang City, amounting to 110 SMEs and there are 56 SMEs that meet the requirements as samples. By using multiple regression analysis concluded that the quality of human resources, marketing systems and partnerships affect the development of SMEs. In order to improve SME development, SME owners need to pay attention to HR competencies by involving employees in training activities on SME management, owners also pay attention to the marketing system by developing marketing information technology in addition to strengthening partnership with external parties.